Protestant Techniques of Care: The Hindu, the Pentecost, and the "Secular". (12th February 2019) - Whitmarsh, Ian
Abstract: Modern techniques of caring for the self through staying healthy rely on an ethic of choice, often evoking critiques of the (neo)liberal subject. This sense of choice has carried frequently overlooked Protestant commitments from Luther to Kant and Locke to 19th‐century American health reformers, premised on a refusal of ritual, mysticism, and the priest as the source of truth. This article explores how these implicit commitments shape the relation to other religious traditions in countries like Trinidad. Campaigns against chronic disease in Trinidad carried out in public health venues and churches echo multinational health projects in pronouncing, "We all want a healthy life." The article draws on a Caribbean ironic sense of secularity to analyze the way that the threat to this "want" found in other religious traditions such as Pentecostal healing and Hindu ecstatic practices reveals Protestant commitments masked within a modern global "secular" care of the self.